METHODOLOGY AND PRACTICE OF TEACHING ENGLISH (Academicia Globe: Inderscience Research, 2023)
This article about teaching English by using interactive methods. In this article it is spoken about a lot of interactive methods, especially the importance of using TPR method in teaching English